A galectin from Hyriopsis cumingii involved in the innate immune response against to pathogenic microorganism and its expression profiling during pearl sac formation. (September 2016) - Bai, Zhiyi; Zhao, Liting; Chen, Xiajun; Li, Qingqing; Li, Jiale
Abstract: Hyriopsis cumingii is the most important freshwater pearl mussel cultured in China. The operation for implantation is one necessary technical step for pearl culture. However, implantation-induced trauma results in a series of immune responses and can enable the invasion of pathogenic microbes. Lectin proteins are found widely in nature and play important roles in innate immunity. Galectins are members of the lectin superfamily and are characterized by one or several carbohydrate recognition domains (CRDs) that produce multiple sugar binding sites on the protein. Here we cloned and characterized the H. cumingii galectin gene HcGal1, which encodes a 312 amino acid galectin protein. The HcGal1 transcript was detected in all tested H. cumingii tissues and showed higher expression specifically in immune tissues. The significant upregulation of HcGal1 expression was observed after challenging the mussel with lipopolysaccharide or Gram-negative and Gram-positive bacteria. After implantation, significant downregulation of the HcGal1 transcript was noted in the mantle, hemocytes, and pearl sac in the acute-stress stage (0–24 h) and the stage of wound healing and pearl-sac formation (24 h–7 d). In addition, significant upregulation of HcGal1 expression was observed in the liver in the stage of wound healing and pearl-sac formation. In the pearl-secretion stage (7–35 d), the HcGal1 transcript levels returned to normal in all tested tissues. We also show that recombinantly expressed and purified HcGal1 can agglutinate some Gram-negative and Gram-positive bacteria. In addition, in vivo experiments showed that the recombinant protein HcGal1 could promote phagocytosis by hemocytes. Our data suggest that HcGal1 plays a role in innate immune responses involved in pathogen recognition and wound healing. Highlights: HcGal1 is expressed in various tissue types and expressed higher in immune tissues especially. HcGal1 expression is induced by bacterial, lipopolysaccharide and implantation treatments. HcGal1 protein can agglutinate some Gram-negative and Gram-positive bacteria.